ANALISIS PENCAPAIAN INDIKATOR 9 CAKUPAN PROGRAM KESEHATAN IBU DAN ANAK (KIA) DI WILAYAH KERJA PUSKESMAS KALIBAGOR KECAMATAN KALIBAGOR KABUPATEN BANYUMAS - Colti Sistiarani; Elviera Gamelia (Kesmas Indonesia, 2012)
ABSTRACT Maternal and Child Health (MCH) program is one of the priority establishment in Indonesia. One of the goals this program is reducing morbidity also mortality in maternal and child. Effort government for maternal and child health to inspect in every area. Data from Banyumas Health Centers still found the maternal and child mortality at Kalibagor Public Health Center, in 2009 there is 2 cases maternal mortality and 13 cases baby mortality. This research aims to analysis 9 coverage maternal and child health programs. This research was a descriptive study with conducted to achieve the coverage target. Result of this research are coverage of the first antenatal care (K1) 92,6%, coverage of the fourth antenatal care (K4) 83,5%, coverage of high risk for maternal 86,2%, coverage of health provider to help delivered baby 82,2%, coverage of maternal after delivered baby 80,7%, coverage of neonatal service 85,7%, coverage of sick child under five years service 93,4%. From this data we know that the achieve are good status. Unfortunately we find achieve coverage status are lack, there is coverage of obstetric complication 57,4% and coverage of maternal and child health book 65%. Conclusion needed effort to increasing coverage of obstetric complication and coverage of maternal and child health book, support was needed from Banyumas Health Centers especially to monitoring and evaluation maternal and child health programs. Key words : Coverage, Maternal and Child Kesmasindo. Volume 5, Nomor 2, Juli 2012, hlm. 95- 120